PENGARUH LEVERAGE, CAPITAL INTENSITY, DAN INVENTORY INTENSITY TERHADAP CASH EFFECTIVE TAX RATE - Andrea Putri Kirana (2021)
The purpose of this study is to determine and prove the effect of leverage, capital intensity, and inventory intensity on tax avoidance as measured by cash effective tax rate. The objects in this study are energy sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2016 - 2019. There are 22 companies with a total 88 data selected as samples through purposive sampling technique. This study uses quantitative methods and panel data. This study analyzes the data and testing the hypothesis through a panel data estimation model determination test and shows the results that the common effect is a suitable model to be used for this study, classical assumption test, panel data regression, coefficient of determination test, and partial test (t test). This study shows the results that with a significance level of 5% there is a significant positive effect of leverage and inventory intensity on the cash effective tax rate, and with a significance level of 10% there is a significant negative effect of capital intensity on the cash effective tax rate.